Effects of chatbot integration in customer service on the level of satisfaction among millennial consumers of telecommunication companies in Tacloban City - Catuday, Arlan A.; Dacuyan, Flordeliz B.; Dominice, Myrlyn Rose A.; Malinao, Kaye Margareth M. (2024)
Chatbot integration in business operations enhances efficiency and cost effectiveness. However, certain drawbacks have led to dissatisfaction. Several studies have assessed consumer perception toward chatbot, but research focused on millennial consumers and the telecommunication sector in Tacloban City is sparse. This study examines the effects of chatbot integration on customer satisfaction among millennial consumers in Tacloban City. Online survey questionnaires were administered to 150 millennial respondents from Tacloban City, who were selected through convenience sampling. In the study, the majority of the respondents were classified as intermediate and advanced technology users which implies that millennial consumers are adept at navigating digital technology. Using a descriptive-correlational research design, it was discovered that beginner users showed a dissatisfied perception towards chatbot use, while intermediate and advanced users were indifferent. In addition, intermediate and advanced technology users exhibited satisfied behavior with chatbot integration in customer service, while beginners were dissatisfied. Moreover, respondents were satisfied with the chatbots' responsiveness and usability but were indifferent with reliability, assurance, and information accuracy, and dissatisfied with empathy. Reliability, assurance, usability, and information accuracy exhibited a strong positive relationship toward customer satisfaction with a correlation coefficient of 0.632, 0.557, 0.612, and 0.585 respectively. Responsiveness showed a moderate positive relationship with a correlation coefficient of 0.417. Conversely, empathy exhibited only a weak positive relationship with a correlation coefficient of 0.229. It was clear from the findings of the study that chatbot integration positively affects customer satisfaction.
Undergraduate thesis (B.S. Management) -- University of the Philippines, Tacloban.